Marriage Dissolution through Divorced Women’s Voices: New Insights from Bangladesh - Md Abdul Jalil (Journal of Asian Social Science Research, 2025)
Abstract Divorce is widely recognized as one of the most stressful life experiences, with far-reaching effects on individuals, families, and society. At the same time, for some women, it may offer relief from oppression and a route to restored autonomy and dignity. This study aimed to explore how divorced women perceive the dissolution of their marriages and how they evaluate the decision to divorce in Bangladesh. Using a qualitative design, semi-structured interviews were conducted with divorced women, and their narratives were analyzed thematically. The findings suggest that marital breakdown is shaped by a cluster of social and relational drivers, including women’s access to education and formal employment, rising expectations for autonomy and empowerment, polygamy, extramarital affairs, interference by in-laws in personal and family life, addiction to social media, and the influence of a wife’s parental family. Although divorce was sometimes framed as a necessary response to persistent inequity and conflict, many participants also reported regret and self-blame for the breakdown of their marriages. The study concludes that prevention efforts should balance respect for women’s agency with initiatives that strengthen mutual respect, communication, and boundary management within extended family systems. This research contributes women-centred evidence to the divorce literature in comparable socio-cultural settings. Implications include expanding community education and couple- and family-focused support services that address polygamy, infidelity, and technology-related tensions while promoting equitable gender relations.